Comparative analysis of BRAF, NRAS and c‐KIT mutation status between tumor tissues and autologous tumor cell‐lines of stage III/IV melanoma. Issue 1 (8th December 2014) - Knol, Anne‐Chantal; Pandolfino, Marie‐Christine; Vallée, Audrey; Nguyen, Frédérique; Lella, Virginie; Khammari, Amir; Denis, Marc; Puaux, Anne‐Laure; Dréno, Brigitte
Abstract In the last decade, advances in molecular biology have provided evidence of the genotypic heterogeneity of melanoma. We analysed BRAF, NRAS and c‐KIT alterations in tissue samples from 63 stage III/IV melanoma patients and autologous cell‐lines, using either allele‐specific or quantitative PCR. The expression of BRAF V600E protein was also investigated using an anti‐BRAF antibody in the same tissue samples. 81% of FFPE samples and tumor cell‐lines harboured a genetic alteration in either BRAF (54%) or NRAS (27%) oncogenes. There was a strong concordance (100%) between tissue samples and tumor cell‐lines. The BRAF V600E mutant‐specific antibody showed high sensitivity (96%) and specificity (100%) for detecting the presence of a BRAF V600E mutation. The correlation was of 98% between PCR and immunohistochemistry results for BRAF mutation. These results suggest that BRAF and NRAS mutation status of tumor cells is not affected by culture conditions.